A novel missense mutation in the NYX gene associated with high myopia. (14th February 2013) - Yip, Shea Ping; Li, Choi Chu; Yiu, Wai Chi; Hung, Wing Hong; Lam, Wai Wa; Lai, Man Chi; Ng, Po Wah; Fung, Wai Yan; Chu, Patrick HW; Jiang, Bo; Chan, Henry HL; Yap, Maurice KH
Abstract Purpose Myopia is a complex eye disorder. The X‐linked form of complete congenital stationary night blindness (CSNB1A) is usually associated with moderate to high myopia, and is caused by mutations in the NYX gene. We explored if NYX mutations could be associated with high myopia, but not CSNB1A. Methods The coding regions of the NYX gene were sequenced for 204 Chinese males with high myopia (−8.00 dioptres or worse for both eyes). The frequencies of any sequence variations identified were determined in 200 Chinese males without myopia. Electro‐oculography, electroretinography and standard cone function tests were performed on a male high myope carrying a mutation. Results A missense mutation (c.529_530GC>AT or p.Ala177Met) was identified in one male subject with high myopia, but not in 200 male emmetropes. Neither was this variant found in any of the 529 male and 567 female subjects of various ethnic backgrounds whose genome sequences are documented in the 1000 Genomes Project database. The mutation was predicted to affect the protein function. From ocular electrophysiological tests, the proband was found to have normal rod function, but mildly abnormal cone function and inner retina function. He did not seem to suffer from CSNB1A. Conclusions One novel missense NYX mutation was identified in an adult male presented with high myopia, but without the major electrophysiological features normally associated with CSNB1A. NYX gene mutations may be considered as one of the rare genetic risk factors for high myopia without key features of CSNB1A.